Unexpected Insights: Raw Sub-Bituminous Coal Outperforms Gamma-Irradiated Coal in Bio-solubilization with Phanerochaete chrysosporium - Arina Findo Sari; Zharifa G Rasul; Jamela B Sampulna (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to investigate the effect of gamma irradiation treatment on sub-bituminous coal in the bio-solubilization process using Phanerochaete chrysosporium and to characterize the bio-solubilization products of raw and irradiated coal under laboratory conditions. Methodology: This study used sub-bituminous coal from South Sumatra, gamma irradiated with an Irpasena irradiator, and biosolubilized with Phanerochaete chrysosporium. Instruments included a Precision® shaker incubator, Novel® microscope, Hanna® pH meter, Shimadzu® GC-MS, and Shimadzu® UV-Vis spectrophotometer. Data were analyzed statistically using T-test with SPSS version 20 software. Main Findings: The results revealed that raw coal exhibited higher solubilization efficiency compared to irradiated coal, indicated by a greater increase in soluble phenolic (0.95 mg/mL) and aromatic compounds (1.42 mg/mL), as well as higher protein production. GC-MS analysis confirmed that raw coal generated more diverse and abundant metabolites, including phenolic and aromatic derivatives, while irradiated coal produced fewer compounds. Statistical analysis (T-test, p < 0.05) supported the significant differences between treatments. These findings suggest that gamma irradiation does not enhance, and may even inhibit, coal bio-solubilization .. Novelty/Originality of this study: This study provides new evidence that gamma irradiation does not enhance, but rather reduces, the bio-solubilization efficiency of sub-bituminous coal by Phanerochaete chrysosporium. The findings challenge the common assumption about irradiation benefits and contribute to advancing knowledge by highlighting the superior performance of raw coal in producing energy-equivalent products.